2022
DOI: 10.1177/15589447211063543
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Clinical Practice Guidelines on Preoperative Antibiotic Administration for Carpal Tunnel Release

Abstract: Background: In 2015, the American Association of Plastic Surgeons (AAPS) published a consensus statement against the routine use of preoperative antibiotic prophylaxis to prevent surgical site infection in clean hand surgery. The American Academy of Orthopaedic Surgeons (AAOS) similarly cited “insufficient evidence” in its Appropriate Use Criteria guidelines to support the use of antibiotics in carpal tunnel surgery. Nonetheless, its administration remains a common practice during clean hand surgery. We sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In our review, only 0.2% of patients ( n = 24/14,255) demanded new surgical procedures and/or hospitalization related to SSI [ 4 , 15 , 16 , 19 23 ]. Also, the prescription of preoperative prophylactic antibiotics had no impact on the incidence of SSI when compared with the administration of placebo or no prophylaxis (RR = 1.13; 95% CI 0.91–1.40; z = 1.1; p = 0.28).…”
Section: Discussionmentioning
confidence: 98%
“…In our review, only 0.2% of patients ( n = 24/14,255) demanded new surgical procedures and/or hospitalization related to SSI [ 4 , 15 , 16 , 19 23 ]. Also, the prescription of preoperative prophylactic antibiotics had no impact on the incidence of SSI when compared with the administration of placebo or no prophylaxis (RR = 1.13; 95% CI 0.91–1.40; z = 1.1; p = 0.28).…”
Section: Discussionmentioning
confidence: 98%
“…Zheng and Fowler further corroborated this information and reported that prophylactic antibiotic administration did not lower the rate of surgical site infection in cubital tunnel surgery 50 . Even so, in a retrospective chart review, 48.2% of patients still received prophylactic antibiotics before CTR surgery from 2017 to 2018 51 . However, this is an improvement from before the guidelines went into effect, when 83.9% of patients received antibiotics before CTR.…”
Section: Infectionmentioning
confidence: 99%